PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Siti Nur Syifa Isnaeni Kurnia (Ta`Limuna: Jurnal Pendidikan Islam, 2023)
Abstract: This study aims to determine the implementation and implications of the jigsaw cooperative learning model in increasing student motivation. The approach used in this study is a qualitative approach. The results obtained by researchers are: 1) the implementation of the jigsaw type of cooperative learning at MAN 2 Karawang, which is applied in learning Aqidah Akhlak and in accordance with the implementation of learning with the jigsaw type in general, 2) the implications of the jigsaw type method for collaborative learning activities that can motivate students to learn. The findings of the novelty of this study are that cooperative learning with the jigsaw type can increase student learning motivation in the form of motivation to understand the material in depth so that they become experts in the material, motivation to work together, and motivation to be able to convey information to others appropriately.